دور إدارة مخاطر الائتمان في تحسين الأداء المصرفي دراسة مسحية في المصرف التّجاري السّوري بمدينة اللاذقية - مرهج منذر; الخيّر نورا (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف البحث إلى التعرف على دور إدارة مخاطر الائتمان في تحسين الأداء المصرفي في المصرف التّجاري السّوري بمدينة اللاذقية. ولتحقيق أهداف البحث تمّ بناء استبانة وتوزيعها على جميع العاملين في إدارة الائتمان في المصرف البالغ عددهم(33)عاملاً, وبعد الدّراسة والتّحليل تمّ التوصل إلى النتائج التالية: 1- تتمتع إدارة الائتمان في المصرف بكفاءة عالية, حيث تقوم باختيار العناصر البشرية العاملة في منح الائتمان من المؤهلين وذوي الخبرة, و تقوم بتحديد حجم الائتمان المناسب لكل عميل, كما تخضع كل عملية ائتمانية لتحليل دقيق ومعاينة شاملة من قبل محلل ائتمان مؤهل وذو خبرة ومعرفة بحجم التّعاملات. 2- تقوم إدارة الائتمان في المصرف من أجل الحفاظ على مستوى سيولة المصرف بتعديل معايير منح الائتمان بالشّكل الذي يؤدي إلى تحسين مؤشرات السّيولة, حيث يحتفظ المصرف بنسبة سيولة طوعية مناسبة من العملات المحلية والأجنبية لأن السيولة الجيدة للمصرف تسهم في زيادة ثقة العملاء في المصرف وعملياته. 3- تقوم إدارة الائتمان في المصرف بتقييم ربحية المصرف بشكل كمي وموضوعي, ومراجعة معايير منح الائتمان بشكل مستمر, وتعديل معايير منح الائتمان بالشكل الذي يساهم في تحسين ربحية المصرف. 4- هناك علاقة طردية بين كفاءة إدارة مخاطر الائتمان, و( انخفاض حجم وعدد القروض المتعثرة, تحسن سيولة المصرف, تحسن ربحية المصرف). The research aims to know the role of credit risk management in the improvement of the banking performance in the commercial bank of Syria in Lattakia. To achieve the research objectives, a questionnaire was constructed and distributed to all credit management employee of the bank, (33 employees). After the study and analysis, the following conclusions were reached: 1- The credit management has a high efficiency, as it defines the appropriate size of credit regarding each client; it chooses the qualified and experienced people to work in the credit management, and each credit transaction get under specific analysis and comprehensive review by a qualified and experienced credit analyst. 2- In order to maintain the level of liquidity of the bank, the credit management amends granting credit criteria, to lead to the improvement of liquidity indicators, where the bank keeps appropriate voluntary liquidity in local and foreign currencies, because the good liquidity in the bank contribute to increase clients’ confidence in the bank and its operations. 3- The credit management in the bank assesses the profitability in quantitive and objective way, and reviews the criteria of the granting on an ongoing basis, and modifies granting credit criteria in a way that lead to improve bank’s profitability. 4- There is a direct correlation between the efficiency of credit risk management and,(low volume and number of non performing loans, improvement of bank’s liquidity ratio, and improvement of bank’s profitability).